Eco-Friendly Marketing: The Market Potential For Sustainably Managed Wooden Products - Home & Office Furniture, In Indian Scenario (Trinity Journal of Management, IT & Media (TJMITM), 2014)
ABSTRACT The purpose of this paper is to study the possibility of promoting wooden  furniture for houses and offices, coming from sustainable managed  forests, in order to support Indian enterprises and the Institutions of the  Indian wooden furniture for houses and offices involved by applying  effective green marketing methods. This research design is based on a  prototype structured questionnaire, according to objective of the  research, 55 responses were collected from Indian wooden furniture  stores for houses and offices, enterprises in 2012. The questionnaires  were analyzed with the statistical program SPSS, using descriptive  statistics and correlation analysis. The main aim was the investigation  of use, knowledge and promotion of wooden furniture for houses and  offices that emanates from forests that are under sustainable  management, and thus planning the green marketing of these products. The Indian enterprises of the wooden furniture for houses and offices  expressed a great concern for the protection of forests. Majority strongly  supports the certification of a sustainable management of Indian forests.  The enterprises believe that the movement of green buildings moves with  a slow pace and forecast that eco consumers are prone to offer an  additional of around 6% on price in order to buy wooden furniture for  houses and offices. A high percent of most Institutions of Education  promote that they use wooden furniture for houses, hostels and offices,  and propose their image building through newspapers, magazines,  Internet portals, websites, etc of high approach. This research study  discusses reflections and forecasts on the growth of this new market of  wooden furniture for houses and offices. It offers valuable insights on  the market of wooden furniture for houses and offices, and also future  developments in the coming years, which can support both enterprises  and the institutions involved in strategy forming and decision making, to  surmount an important share of the market of eco consumers. The study  also proposes an effective method of eco marketing applications.
Keywords: Green Marketing; Forest Sustainability; Marketing Planning; Timber Markets; Marketing Research; Ethics; Environment-friendly; Wooden Products; Furniture